Análisis de amenaza, vulnerabilidad y riesgo en la cuenca alta del Río Bogotá, en el Municipio de Villapinzón, utilizando modelación hidrológica HEC-HMS e hidráulica 1D y 2D HEC-RAS e ÍBER (2015)
Initially the importance of the study area is highlighted, which makes evident the damages caused by phenomena of increasing and how the planning plays an important role in preventing them. Also cited a weather and rains in the area under study analysis. Then a hydrologic analysis is performed in the upper basin of the Bogotá River on the sector Villapinzon based on computational tools Hec-Hms. Then one-dimensional and twodimensional modeling was performed in Hec-Ras and Iber, the Bogota River bordering the urban area Villapinzón, commonly used in modeling rivers, but which has been focused in this paper the analysis of threat flood and vulnerability of structures, homes and agricultural land. Finally, the analysis of risks to which the municipality is exposed by the phenomenon of growing and the damages or losses they may cause in the town of Villapinzon presented.